Developing STEM Electronic Student Worksheet with Problem-Based Learning to Enhance Communication Skills - Rahayu, Murih; Distrik, I Wayan; Suyatna, Agus (Universitas Islam Negeri Raden Intan Lampung, 2023)
This research aimed to develop STEM-integrated Problem-Based Learning e-worksheets to enhance students' communication skills. The research methodology employed was research and development (R&D). The development process followed the instructional design model ADDIE, which consists of five stages: analysis, design, development, implementation, and evaluation. Upon conducting research and analysis, the results indicated high satisfaction with the validity of the STEM-integrated problem-based e-worksheets in terms of content and construct. The average content aspect percentage was 88%, while the construct aspect percentage was 87%. The effectiveness of the e-worksheets was demonstrated through N-gain results and paired t-tests, revealing a notable improvement in communication skills. In conclusion, the developed Problem-Based Learning e-worksheets integrated with STEM effectively enhanced students' communication skills. These findings hold significant value for the learning process, particularly in enhancing students' communication skills and providing teachers of physics with additional e-worksheets as valuable learning resources. It is expected that further development of these e-worksheets will contribute significantly to enhancing students' overall communication skills.